Pemanfaatan Layanan Pojok Baca Digital sebagai Sumber Belajar bagi Siswa di Perpustakaan SMA Negeri 2 Painan - Liodi, Vina Rahma; Desriyeni, Desriyeni (Scinary, 2023)
This studi aims to find out how the utilization of digital reading corner services as a learning resource for students at SMA Negeri 2 Painan Library. The purpose of this study is to describe. First, the utilization of digital reading corner services by students of SMA N 2 Painan. Second, student learning resources by utilizing digital reading corner services at SMA N 2 Painan Library. This study used quantitative descriptive method. This study had a population of 1,247 students with a sample drawn amounting to 92 students. The data that has been collected is made into a table form and then data processing is carried out with calculations using the mean formula and grand mean calculations to calculate the total average of each indicator and variable. Based on the results of the study, results were obtained. First, the utilization of digital reading corner services by SMA Negeri 2 Painan students obtained an average score of 3.04 with an interval scale of 2.52 –3.27 in the high category. Second, student learning resources by utilizing the digital reading corner service at SMA Negeri 2 Painan Library obtained an average score of 3.05 in the high category.